Possibilities of refinement of hot water recirculation system in terms of energy demand - Fijewski, Michał (Instal, 2023)
The article presents an analysis of data showing the operation of a circulation system in a multi-family residential building. It also presents detailed guidelines and an assessment of their impact on the quality of the circulation pump’s operation. The article discusses the impact of a hot water circulation system on the EP primary energy index and the concept of programme control in a hot water circulation system with an overview of devices for programme control of pump operation. In the research part, the characteristics of the building in which measurements of its hot water preparation system were made were presented. The results of the measurements were developed and presented in the form of graphs which enable the evaluation of the quality of operation of the domestic hot water preparation system and the estimation of the possibility of controlling the circulation installation. The final part of the article presents guidelines for improving the energy efficiency of hot water circulation installations, such as selection of the control device, its connection to the system, and operating guidelines. An evaluation of the energy improvement in the quality of the circulation installation was also carried out on the basis of the impact of the introduced control method on the EP index as well as electricity consumption and costs.
Keywords: hot water circulation; circulation system; circulation pump; program control